A Characterization of Global Entanglement. - Love, Peter J.; Van Den Brink, Alec Maassen.; Smirnov, A.Yu.; Amin, M.H.S.; Grajcar, M.; Il'ichev, E.; Izmalkov, A.; Zagoskin, A.M. (Tufts University. Tisch Library., 2018)
We define a set of 2 n-1-1 entanglement monotones for n qubits and give a single measure of entanglement in terms of these. This measure is zero except on globally entangled (fully inseparable) states. This measure is compared to the Meyer-Wallach measure for two, three, and four qubits. We determine the four-qubit state, symmetric under exchange of qubit labels, which maximizes this measure. It is also shown how the elementary monotones may be computed as a function of observable quantities. We compute the magnitude of our measure for the ground state of the four-qubit superconducting experimental system investigated in [M. Grajcar et al., Phys. Rev. Lett. 96, 047006 (2006)], and thus confirm the presence of global entanglement in the ground state. © Springer Science+Business Media, LLC 2007.